Left Lateral Table Tilt for Elective Cesarean Delivery Under Spinal Anesthesia Has No Effect on Neonatal Acid-Base Status. Issue 2 (June 2018) - Lee, A.J.; Landau, R.; Mattingly, J.L.; Meenan, M.M.; Corradini, B.; Wang, S.; Goodman, S.R.; Smiley, R.M.
Abstract : ( Anesthesiology . 2017;127(2):241–249) Cesarean delivery in the supine position may result in maternal hypotension, aortocaval compression, and fetal complications. Uterine displacement by left lateral tilt is currently recommended to prevent these outcomes. Tilting was associated with superior neonatal acid-base status in studies during the 1970s. The current use of vasopressor agents to effectively prevent maternal spinal hypotension calls into question the necessity of tilting, particularly since the target tilt of 15 degrees is rarely achieved. This study hypothesized that, using a fluid coload with spinal anesthesia and a phenylephrine infusion to maintain baseline systolic blood pressure, neonatal acid base status would not be affected by maternal position (supine vs. tilted) in women delivering via elective cesarean delivery.